Modifikasi Atau Modernisasi (?): Permainan Anak di Sekolah Kartini Semarang - Galuh Ambar Sasi; Emy Wuryani; - Sunardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
This paper examines the children's playings at Kartini School Semarang. By Combining the annual reports, memorial albums, colonial magazines and newspapers, archives, literature, ego documents, then approached with history of mentality perspectives, we point out that they developed following Froebel's education system. Therefore, they integrated into the curriculum for the 1st-3rd grade, unlimited by type, philosophy, languages, or its influence on students, while the school resembled a children's playground.